Morphological and molecular evolution of hadal amphipod’s eggs provides insights into embryogenesis under high hydrostatic pressure - Li, Wenhao; Wang, Faxiang; Jiang, Shouwen; Pan, Binbin; Liu, Qi; Xu, Qianghua (Frontiers in Cell and Developmental Biology, 2022)
Hadal zones are unique habitats characterized by high hydrostatic pressure (HHP) and scarce food supplies. The ability of eggs of species dwelling in hadal zones to develop into normal embryo under HHP is an important evolutionary and developmental trait. However, the mechanisms underlying the development of eggs of hadal-dwelling species remain unknown due to the difficulty of sampling ovigerous females. Here, morphological and transcriptome analyses of eggs of the “supergiant” amphipod Alicella gigantea collected from the New Britain Trench were conducted. The morphology of A. gigantea eggs, including size, was assessed and the ultrastructure of the eggshell was investigated by scanning electron microscopy. Transcriptome sequencing and molecular adaptive evolution analysis of A. gigantea eggs showed that, as compared with shallow-water Gammarus species, genes exhibiting accelerated evolution and the positively selected genes were mostly related to pathways associated with “mitosis” and “chitin-based embryonic cuticle biosynthetic process”, suggesting that “normal mitosis maintenance” and “cuticle development and protection” are the two main adaptation strategies for survival of eggs in hadal environments. In addition, the concentration of trimethylamine oxide (TMAO), an important osmotic regulator, was significantly higher in the eggs of hadal amphipods as compared to those of shallow-water species, which might promote the eggs’ adaptation abilities. Morphological identification, evolutionary analysis, and the TMAO concentration of A. gigantea eggs will facilitate a comprehensive overview of the piezophilic adaptation of embryos in hadal environments and provide a strategy to analyze embryogenesis under HHP.